Case Report: Occurrence of Thyroid Storm in a Young Patient With Recurrent Diabetic Ketoacidosis - Iino, Tatsuya; Akatsuka, Masayuki; Yamamoto, Shuji (Frontiers in Endocrinology, 2022)
Background: Thyroid storm (TS) is a fatal disease that leads to multiple organ failure and requires prompt diagnosis. Diabetic ketoacidosis (DKA) is a trigger for thyroid crisis. However, TS and DKA rarely occur simulatenously. Moreover, owing to the rarity of the co-occurrence, the clinical course remains unclear. In this study, we present a case of TS that developed during the follow-up for repeated DKA in a young patient. Case presentation: A 25-year-old man with a history of recurrent DKA was brought to the emergency room frequently with similar symptoms. DKA treatment was initiated, but his tachycardia and disturbance of consciousness did not improve. Further examination of the patient revealed a Burch–Wartofsky Point Scale score of 80 points, consistent with the Japan Thyroid Association criteria. Therefore, DKA coexisting with TS was diagnosed. Antithyroid medication, inorganic iodine, and corticosteroids were then started as treatment for TS, and β-blockers were administered for managing tachycardia. With these treatments, the patient’s health improved and he recovered. Conclusions: In severe cases of recurrent DKA, the presence of TS should be considered, and early treatment should be initiated before the patient’s condition worsens.